Chora and the resurgence of the sensuous - Andreescu, Florentina C. (Short Film Studies, 2016)
Abstract This article reads Kid as Little Man’s connection to chora, the primordial maternal space where language is experienced as a phenomenon akin to birdsongs and animals’ howls, through which Little Man is inscribed into the world’s wild rhythms of movement and sound, and explores how this connection distorts the cinematic space.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9zZnMuNi4xLjc1XzE